“Genius equall to that which wrought another most beautifull Poem”: classical communication in the writings of Mercy Otis Warren and Judith Sargent Murray - Wolgast, Sydney Marie (My University, 2024)
This research examines how two colonial American women, Mercy Otis Warren and Judith Sargent Murray, utilized classical history and literature within their own writings before, during, and after the War for Independence. Through their poems, plays, and essays, they sought to both rally and educate the masses. Warren hoped to inspire colonists to fight against tyranny while maintaining their virtues and Murray used the momentum of the war to fight for equal education opportunities between the sexes. This paper analyses the specific works containing references to ancient Greek and Roman literature and history to better understand the comparisons and allusions being made within each text
Keywords: Mercy Otis Warren; Judith Sargent Murray; Classics; American Revolution; Poems